Research into the Degree of Impact Made by Explication of Various Ethnic Stereotypes During the Educational Process - Elena A. Golubovskaya; Nikolay V. Butylov; Galina A. Khorokhorina (National Research Mordova State University, 2018)
Introduction. The article explores the impact of various types of verbal representation of ethnic stereotypes in the framework of a polyethnical academic community, i.e. educational environment in modern international university. Although the educational process with subjects of different cultural backgrounds plays a crucial role in conveying world views of representatives of different cultures, the research on the linguistic representation of stereotyped views on representatives of other nationalities has not been conducted yet. This aspect determines the relevance of the study. The aim of the research is to compare the impact levels of purely linguistic and speech ways of verbalising heterostereotypes by ways of employing relevant linguistic data for academic purposes during foreign language classes. Materials and Methods. The first stage of the experiment resulted in preparation of the linguistic corpus for the research: by means of comprehensive vocabulary research the lexical database with ethnonyms or ethnonym-based adjectives was compiled. To reveal the potential of their usage in the education processes, the participants were offered the preliminary and final surveys held as free associatio n experiment. Results. The influential potential for purely linguistic and speech ways of representing national stereotypes was compared to find out if they relate to the descriptors and scripts revealed through analysis of phraseological units and national anecdote respectively, while the latter was marked as a more efficient way of delivering ethnic stereotypes. The conclusions based on the analysis of the data obtained were drawn on how to use relevant linguistic material for academic purposes in order to appropriately develop attitudes to other ethnic groups. Discussion and Conclusions. The conducted research revealed more significant impact degree for ethnic anecdotes against investigation of lexical-phraseological units containing ethnonyms or ethnonym-based adjectives. It was illustrated by collection and further analysis of verbal reactions provided by students of non-linguistic departments of the modern University who took part in the preliminary and final stages which were in line with the beginning and end of the academic term accordingly. The portraits of typical national representatives made by the students at the completion of the course which included sessions on studying dictionary extracts and national anecdotes, to a greater extent conformed with the stereotypes delivered by ethnic anecdotes than the linguistic corpus of lexical-phraseological units. The research results may be considered during the development of the curriculum for foreign language courses in international universities with polyethnical academic environment.